2020
DOI: 10.3389/fnagi.2020.603340
|View full text |Cite
|
Sign up to set email alerts
|

Which Parameters of Beat-to-Beat Blood Pressure Best Predict Poor In-Hospital Outcome in Spontaneous Intracerebral Hemorrhage?

Abstract: Objective: There is increasing evidence that high blood pressure (BP) levels and BP variability (BPV) over 24 h or longer are associated with poor clinical outcomes in patients with intracerebral hemorrhage (ICH). The objective of this study was to examine the association between different beat-to-beat BP parameters and in-hospital outcomes. Methods: Patients with a diagnosis of acute spontaneous ICH were recruited consecutively and prospectively between September 2018 and January 2019. Beat-to-beat recordings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Sykora et al [11,30] found that 72-h beat-to-beat mean arterial pressure variability was related to relative oedema and 10-day outcome in a univariate analysis; however, the result was not duplicated in a stepwise multivariate linear regression analysis. We previously demonstrated in an earlier report from acute spontaneous supratentorial ICH patients that beat-to-beat BPV derived by SBP was associated with a 2.5fold increase in the risk of poor in-hospital outcomes for every unit of beat-to-beat BPV increase, independent of admission and mean beat-to-beat blood pressure level [31]. The present study further indicated that beat-to-beat BPV, measured 1-2 days after ICH onset, calculated from either SBP or DBP, was associated with unfavourable functional outcomes at 3 months, independent of mean blood pressure.…”
Section: Discussionmentioning
confidence: 88%
“…Sykora et al [11,30] found that 72-h beat-to-beat mean arterial pressure variability was related to relative oedema and 10-day outcome in a univariate analysis; however, the result was not duplicated in a stepwise multivariate linear regression analysis. We previously demonstrated in an earlier report from acute spontaneous supratentorial ICH patients that beat-to-beat BPV derived by SBP was associated with a 2.5fold increase in the risk of poor in-hospital outcomes for every unit of beat-to-beat BPV increase, independent of admission and mean beat-to-beat blood pressure level [31]. The present study further indicated that beat-to-beat BPV, measured 1-2 days after ICH onset, calculated from either SBP or DBP, was associated with unfavourable functional outcomes at 3 months, independent of mean blood pressure.…”
Section: Discussionmentioning
confidence: 88%
“…Previous studies have shown an association between an excessive drop in nocturnal blood pressure and silent cerebrovascular lesions [24,25]. The explanation for this could be pre-existing cerebral ischaemia that could lead to both altered central autonomic control of blood pressure [26,27] and an increased risk of stroke. Furthermore, BP variability is also known to associate with pro-inflammatory cytokine production, hyperglycaemia, and increased blood-brain-barrier permeability [28][29][30][31], all of which can contribute to an increased risk of stroke.…”
Section: Discussionmentioning
confidence: 99%
“…As vaccination becomes more widespread, gradual deregulation of traffic restrictions would effectively improve the prognosis of patients with stroke. Simultaneously, for the high proportion of hypertensive cerebral hemorrhage cases, strengthening the prevention, and control of hypertension before and after ICH is also important ( 28 , 29 ).…”
Section: Discussionmentioning
confidence: 99%